The Impact Of Social Media On Social Behavior Children In The City Of Surabaya - Jarmani, Jarmani (International Journal of Educational Research & Social Sciences, 2024)
The primary issue with this study is how much children who are thought to have a strong interest in character development and child protection use communication media. Children in Surabaya City may be perceived to be influenced by the information and knowledge that the media presents. Qualitative research is the kind that this is. Data is acquired through Three methods: documentation, interviews, and observation. Techniques for data analysis are documented, data is gathered, and analysis is done to give categories meaning. The Snowball Sampling Technique is used to choose and determine research subjects. The snowball sampling technique is a method for selecting and collecting samples within a network or relationship. In Surabaya, a study on children's social and communication media has led researchers to conclude that communication media is necessary for the community, regardless of social class. These days, finding communication media takes a lot of work. The extensive usage of communication media among children and teenagers in the community proves that communication media has also reached all age groups. It cannot be disputed because young people are particularly susceptible to falling prey to the adverse effects of media. Not only may using communication media have significant effects, but it can also have adverse effects that can influence users earlier than youngsters who are quick learners and highly curious. Children's performance can improve if they are given access to unfavorable, unreasonable, or inappropriate things for their age. In this instance, parents' involvement in the supervision process is crucial. Effective communication offers insight into children, obviating the need to do things to adolescents and children, as supportive parents are the primary institution in shaping a child's character, attitude, and behavior.